Identifying genetic susceptibility loci associated with human coronary artery disease - Aqsa Zahid; Andleeb Batool; Abdul Wajid; Yurong Wu; Chun Liang; Muhammad Ajmal Khan; Amin Ullah; Kashif Iqbal Sahibzada; Hong Xue (PLoS ONE, 2025)
Coronary artery disease (CAD) is a multigenic condition influenced by both nature and nurture (60% to 40%). Prognosis of CAD is based on familial patterns. This study examined and analyzed the susceptibility of CAD to genetic variants in various Pakistani families. A total of 50 families, 308 participants (79 affected and 229 unaffected were genotyped for NOS3 (rs1799983, rs2070744), PON1 (rs662), LPA-PLA2 (rs105193, rs1805017), APOE (rs429358, rs7412), PCSK9 (rs505151), MEF2A (rs325400), TNF (rs1800629) and LDLR (rs1122608, rs2228671) genes. The family-based association in CAD associated genes SNPs were NOS3 (rs1799983), PON1 (rs662), LPA-PLA2 (rs1805017), MEF2A (rs325400), and LDLR (rs1122608, rs222867) showed transmission within families p≤ 0.05 whereas NOS3 (rs2070744), APOE (rs429358, rs7412) and TNF (rs1800629) showed no association TDT asymptotic p-value >0.05. In DFAM and QFAM test NOS3 (rs1799983), PON1 (rs662), MEF2A (rs325400), and LDLR (rs1122608, rs222867) showed positive association p≤ 0.05 in both whereas NOS3 (rs2070744), APOE (rs429358, rs7412), LPA-PLA2 (rs1805017) and TNF (rs1800629) showed low risk of transmission asymptotic p-value >0.05 in DFAM but NOS3(rs2070744), APOE(rs7412), LPA-PLAG2(rs1805017) also showed association p≤ 0.05 whereas APOE (rs429358) and TNF (rs1800629) showed no association EMP1 p-value >0.05 in QFAM. In linkage analysis Chromosome 6 (Position 70.810): LOD = 3.16, Chromosome 7 (Position 107.190): LOD = 3.16, and chromosome 19 (Position 31.470): LOD = 3.90 also showed significant association with disease as p < 0.05. This discovery enhances the understanding about genetic variants of CAD and also facilitates early detection, targeted interventions, pattern of inheritance in population. This ultimately improving patient outcomes and guiding future research to highlight its significance as a potential diagnostic marker.